Influence of Crowdsourcing Innovation Community Reference on Creative Territory Behavior - Xiao, Wei; Wang, Xiao-Ling; Cao, Yan-Ning (Frontiers in Psychology, 2022)
Crowdsourcing innovation community has become an important platform for enterprises to gather group wisdom. However, how the crowdsourcing innovation community plays a reference role in creative crowdsourcing participation is unclear. Based on the group reference theory, taking online impression management as the explanatory framework, this study explores the impact of crowdsourcing innovation community reference on the creative territory behavior, and the differences in the crowdsourcing innovation community reference effect among members of different community ages. 524 valid two-stage questionnaires were collected. The empirical analysis results show that under the influence of informational reference and utilitarian reference of crowdsourcing innovation community, community members are significantly more likely to adopt acquired impression management than defensive impression management; under the influence of value expressive reference of crowdsourcing innovation community, the possibility of adopting defensive impression management behavior is significantly greater than that of adopting acquired impression management behavior; compared with defensive impression management behavior, acquired impression management behavior has a more inhibitory effect on creative territory behavior. Interestingly, there are different community reference effects among members of different community ages. In particular, the positive contribution of the elder members is not as good as that of the newcomers. The above research conclusions not only confirm the influence of crowdsourcing community reference on crowd participation decision-making, but also provide theoretical and practical enlightenment for exploring the cooperation mechanism of crowdsourcing innovation.